2002
DOI: 10.1109/36.992801
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of GENIE and conventional supervised classifiers for multispectral image feature extraction

Abstract: We have developed an automated feature detection/classification system, called GENetic Imagery Exploitation (GENIE), which has been designed to generate image processing pipelines for a variety of feature detection/classification tasks. GENIE is a hybrid evolutionary algorithm that addresses the general problem of finding features of interest in multispectral remotely-sensed images. We describe our system in detail together with experiments involving comparisons of GENIE with several conventional supervised cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(46 citation statements)
references
References 28 publications
(18 reference statements)
0
46
0
Order By: Relevance
“…It has been applied in a variety of application domains, including imageprocessing problems. In the field of remote sensing, some works have already demonstrated that this evolution-based process could be useful in particular, to detect and eliminate noisy spectral bands (for hyperspectral images), and to produce comprehensible classification rules [7,8,9,10]. GP can provide relevant and robust rules in terms of classification accuracy.…”
Section: Genetic Programmingmentioning
confidence: 99%
“…It has been applied in a variety of application domains, including imageprocessing problems. In the field of remote sensing, some works have already demonstrated that this evolution-based process could be useful in particular, to detect and eliminate noisy spectral bands (for hyperspectral images), and to produce comprehensible classification rules [7,8,9,10]. GP can provide relevant and robust rules in terms of classification accuracy.…”
Section: Genetic Programmingmentioning
confidence: 99%
“…The first is the approach used in GENIE, an evolutionary system for finding features of interest in multi-spectral remotely-sensed images [13,14]. In this system a set of morphological operators was provided as part of a larger set of image processing primitives.…”
Section: Gas For MM Filters and Algorithm Designmentioning
confidence: 99%
“…However, only some specifi time-series domains have been tested. Similarly, [23,24] assembles image-processing primitives (edge-detectors, . .…”
Section: Related Workmentioning
confidence: 99%